Social Behavior of Student Users of The Mobile Legends Online Game; Case Study - Hasib, Mohammad; Erjayanto, Dea Eka (Program Studi Magister Manajemen Pendidikan, 2024)
Playing online games is an activity that is done for fun without considering the possible consequences of the activity. This study provides an understanding of student behavior towards online games towards academic activists. The type of research used in this study uses a qualitative descriptive approach. The results of the study show 1. Playing online games excessively can affect the psychological condition of students, especially stress, anxiety, and disrupt their mental health, for example, being easily offended, emotional and easily swearing 2. Consumptive behavior of online games results in decreased interest in learning, decreased levels of achievement in terms of daily course results, lateness and attendance at lecture hours, time that should be used for rest and study is actually spent sitting in front of a computer or gadget to play online games. Meanwhile, from the aspect of benefits, it does provide high hallucination satisfaction that is brought into everyday life, and sometimes it can be used as a side business by buying and selling member accounts in online games.Keywords: Online Games, Mobile Legends Bang Bang, Pesikis. DOI: 10.23960/jmmp.v12.i2.2024.30311